Greenness, air pollution, and mortality risk: A U.S. cohort study of cancer patients and survivors. (December 2021) - Coleman, Carver J.; Yeager, Ray A.; Riggs, Daniel W.; Coleman, Nathan C.; Garcia, George R.; Bhatnagar, Aruni; Pope, C. Arden
Highlights: This study evaluated greenness and air pollution on mortality risk of cancer patients and survivors in the U.S. Greenness, as measured by NDVI, was associated with decreased risk of cancer mortality. Air pollution, as measured by PM2.5, was associated with increased risk of cardiopulmonary mortality. Individuals with high survivability cancers were benefited more from greenness than those with low survivability cancers. Abstract: Background: Several studies suggest that living in areas of high surrounding greenness may be associated with a lower cardiopulmonary mortality risk. However, associations of greenness with specific causes of death in cancer patients and survivors has not been examined and it is unknown whether this relationship is affected by area levels of fine particulate matter air pollution (PM2.5 ). This study evaluated associations between greenness and PM2.5 on causes of death in a large, U.S.-based cohort of cancer patients and survivors. Methods: Surveillance, Epidemiology and End Results (SEER) data were used to generate a cohort of 5, 529, 005 cancer patients and survivors from 2000 to 2016. Census-tract Normalized Difference Vegetation Index (NDVI) during May-October from 2003 to 2016 was population-weighted to act as a county-level greenness measure. County-level PM2.5 exposure was estimated from annual concentrations averaged from 1999 to 2015. Cox Proportional Hazards models were used to estimate the association between greenness, PM2.5, and cause-specific mortality while controlling for age, sex, race, and other individual and county level variables. Findings: An IQR increase in greenness was associated with a decrease in cancer mortality for cancer patients (Hazard ratio of 0.94, 95% CI: 0.93–0.95), but not for cardiopulmonary mortality (0.98, 95% CI: 0.96–1.00). Inversely, an increase in 10 μg/m 3 PM2.5 was associated with increased cardiopulmonary mortality (1.24, 95% CI: 1.19–1.29), but not cancer mortality (0.99, 95% CI: 0.97–1.00). Hazard ratios were robust to inclusion of PM2.5 in models with greenness and vice versa. Although exposure estimates were constant over most stratifications, greenness seemed to benefit individuals diagnosed with high survivability cancers (0.92, 95% CI: 0.90–0.95) more than those with low survivability cancers (0.98. 95% CI: 0.96–0.99). Interpretation: Higher levels of greenness are associated with lower cancer mortality in cancer patients. The evidence suggests minimal confounding between greenness and PM2.5 exposures and risk of mortality.